A second-order method for convex 1-regularized optimization with active-set prediction. (3rd May 2016) - Keskar, N.; Nocedal, J.; Öztoprak, F.; Wächter, A.
Abstract : We describe an active-set method for the minimization of an objective function φ that is the sum of a smooth convex function f and an -regularization term. A distinctive feature of the method is the way in which active-set identification and second-order subspace minimization steps are integrated to combine the predictive power of the two approaches. At every iteration, the algorithm selects a candidate set of free and fixed variables, performs an (inexact) subspace phase, and then assesses the quality of the new active set. If it is not judged to be acceptable, then the set of free variables is restricted and a new active-set prediction is made. We establish global convergence for our approach under the assumptions of Lipschitz-continuity and strong-convexity of f, and compare the new method against state-of-the-art codes.